Protein arginine deiminase 2 (PAD2) modulates the polarization of THP-1 macrophages to the anti-inflammatory M2 phenotype - Aneta Stachowicz; Rakhi Pandey; Niveda Sundararaman; Vidya Venkatraman; Jennifer E. Van Eyk; Justyna Fert-Bober (BMC, 2022)
Abstract Background Macrophages are effector cells of the innate immune system that undergo phenotypical changes in response to organ injury and repair. These cells are most often classified as proinflammatory M1 and anti-inflammatory M2 macrophages. Protein arginine deiminase (PAD), which catalyses the irreversible conversion of protein-bound arginine into citrulline, is expressed in macrophages. However, the substrates of PAD and its role in immune cells remain unclear. This study aimed to investigate the role of PAD in THP-1 macrophage polarization to the M1 and M2 phenotypes and identify the citrullinated proteins and modified arginines that are associated with this biological switch using mass spectrometry. Results Our study showed that PAD2 and, to a lesser extent, PAD1 and PAD4 were predominantly expressed in M1 macrophages. We showed that inhibiting PAD expression with BB-Cl-amidine decreased macrophage polarization to the M1 phenotype (TNF-α, IL-6) and increased macrophage polarization to the M2 phenotype (MRC1, ALOX15). This process was mediated by the downregulation of proteins involved in the NF-κβ pathway. Silencing PAD2 confirmed the activation of M2 macrophages by increasing the antiviral innate immune response and interferon signalling. A total of 192 novel citrullination sites associated with inflammation, cell death and DNA/RNA processing pathways were identified in M1 and M2 macrophages. Conclusions We showed that inhibiting PAD activity using a pharmacological inhibitor or silencing PAD2 with PAD2 siRNA shifted the activation of macrophages towards the M2 phenotype, which can be crucial for designing novel macrophage-mediated therapeutic strategies. We revealed a major citrullinated proteome and its rearrangement following macrophage polarization, which after further validation could lead to significant clinical benefits for the treatment of inflammation and autoimmune diseases.